Green the Islamic boarding school: Eco enzyme training for organic waste management - Rendana, Muhammad; Susanti, Susi; Yandriani, Yandriani; Jati, Stevanus Nalendra; Renaldi, Fadhlurrahman; Akbar, M. Naufal (Community Empowerment, 2025)
The issue of organic waste, which predominantly originates from households and is also generated by educational institutions such as schools, has the potential to cause environmental impacts if not managed properly. Organic waste holds significant potential to be processed into eco enzyme, which has various benefits. Recognizing this potential, this community service program aimed to empower the community at Pondok Pesantren At Tauhiid, Indralaya, South Sumatra, through eco enzyme production training. The methodology employed in this activity included lectures and direct practical training. The program results indicated a 60% increase in understanding regarding eco enzyme production after participating in the training, which utilized leftover fruit and vegetable waste. This program is expected to serve as a community empowerment model for independent organic waste management, particularly within educational institution environments.